Cutaneous lupus associated with pembrolizumab therapy for advanced melanoma: a report of three cases. Issue 3 (June 2019) - Blakeway, Elizabeth A.; Elshimy, Noha; Muinonen-Martin, Andrew; Marples, Maria; Mathew, Bipin; Mitra, Angana
Abstract : Checkpoint blockade immunotherapy has revolutionized the treatment of advanced melanoma, with impressive survival benefits attained through upregulation of the anticancer immune response. Blockade of regulatory checkpoint molecules can, however, also result in aberrant immune activation leading to undesirable inflammation and autoimmunity. Although many genetic determinants have been described in patients with primary autoimmune diseases, it is uncertain whether patients developing autoimmune skin disease as an adverse effect of anti-PD-1 therapy share the same genetic risks. Furthermore, it is also unclear whether treatment with these agents can result in the unveiling of underlying 'silent' autoimmunity resulting in chronic inflammatory disease. We report three cases of cutaneous lupus associated with pembrolizumab therapy for advanced melanoma. One patient had a previous diagnosis of histologically proven discoid lupus erythematosus, well-controlled without treatment for over 2 years, which flared on first exposure to pembrolizumab. The remaining two patients had no previous history of autoimmune disease; both developed cutaneous eruptions, histologically and immunohistologically, in keeping with subacute cutaneous lupus following treatment with pembrolizumab. Our report bolsters what is currently an exceedingly small body of evidence documenting the development of cutaneous lupus in the setting of pembrolizumab therapy. Our third case specifically documents an otherwise unreported severe reflare of previously diagnosed, quiescent discoid lupus erythematosus in the setting of pembrolizumab, vividly highlighting the potential for autoimmune and specifically, lupus reactivation in the setting of anti-PD-1 therapy.